Determinan Pengungkapan Corporate Social Responsibility pada Perusahaan Pertanian dan Pertambangan di Bursa Efek Indonesia Tahun 2018-2022 - Permata, Muna Windiya Ega; Cahyono, Yuli Tri (Jayapangus Press, 2024)
Corporate social responsibility changes the focus of a business from internal responsibility to environmental and social issues. This research examines how profitability, liquidity, leverage, independent board of commissioners, managerial ownership, and audit committee impact Corporate Social Responsibility (CSR) in agricultural and mining companies traded on the Indonesia Stock Exchange (BEI) from 2018 to 2022. A total of eight out of a total of 75 companies as observation units, the companies have met the criteria in the purposive sampling method. This analysis uses multiple linear regression. Classic assumption tests such as normality, heteroscedasticity, multicollinearity and autocorrelation were used to process this research data. The research results show empirical evidence that leverage (DER), manager ownership, and audit committee have an effect, while profitability (ROE), liquidity (CR), and board of commissioners do not influence corporate social responsibility. Kolmogorov-Smirnov normality test results with Asymp. Sig. (2-tailed) shows that the data is normally distributed, with a significance value of 0.104 > 0.05. The research results also do not show symptoms of multicollinearity because the tolerance value is above 0.10 and the VIF is below 10. There is no heteroscedasticity problem because the significance value of each independent variable is greater than α (0.05). The research results also show that there is no autocorrelation problem between each regression variable with the Asmpy sig (2-tailed) value being 0.104 more than 0.05. Apart from that, the F test results of the five independent variables influence CSR simultaneously. The results of calculating the coefficient of determination (R2), which shows an R2 value of 0.910. This shows that ROE, CR, DER, board of commissioners, manager ownership and audit committee influence CSR by 91%. Additional factors not discussed in this study had an impact of 9%.